Toward Net Zero: Islamic Financial Innovation in The Carbon Economy - Nanik Eprianti; Mohamad Andri Ibrahim; Popon Srisusilawati; Yayat Rahmat Hidayat (al-Afkar, Journal For Islamic Studies, 2026)
Green finance has gained significant momentum in recent years, but its alignment with Islamic finance principles remains under-explored, particularly in the context of carbon pricing and carbon trading mechanisms. This is illustrated by the fact that climate change has prompted the global community to adopt various strategies, including the development of carbon market mechanisms. Exploring the potential of the carbon market as an effective tool in reducing greenhouse gas emissions, while considering the principles of Islamic finance. This study aims to develop Sharia-based sustainable financial instruments as a strategy to address the impacts of climate change through the utilization of the carbon market.  This research method uses a qualitative approach that combines bibliometric analysis, policy document reviews, and expert interviews. This study identifies critical gaps in the integration of Islamic finance with carbon market mechanisms and the design of sustainable financial instruments that comply with Sharia principles. This study uses a qualitative approach with a descriptive-exploratory method. A qualitative approach is used to understand in depth the concepts, phenomena, and characteristics of Islamic financial instruments and how they can be implemented in the carbon market. The findings show that Islamic finance has great untapped potential to mobilize ethical capital and share risks for climate-friendly projects, especially in Muslim-majority countries and emerging economies. Nevertheless, regulatory standardisation, sharia governance frameworks, and investor education remain key challenges that must be addressed to enhance the scalability and credibility of such instruments. By bridging the gap between Islamic finance and carbon economy strategies, this study contributes to the growing discourse on green Islamic finance and offers practical policy recommendations to strengthen the role of Islamic financial institutions in achieving both national and global net-zero targets.